Lembaga Penyiaran Publik Radio Republik Indonesia dan Implementasi Kebijakan (Studi Kasus Radio Republik Indonesia Banjarmasin Mengimplementasikan Peraturan Pemerintah Nomor 12 Tahun 2005 tentang Lembaga Penyiaran Publik Radio Republik Indonesia di Tahun 2013) - , syarifuddin, Dr. Phil. Ana Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the Communications policy to be applied in broadcasting is government regulation Peraturan Pemerintah number 12 in 2005 (PP No. 12 Tahun 2005) about public broadcasting institute âLembaga Penyiaran Publik Radio Republik Indonesiaâ (LPP RRI). It has been happen since eight years but few aspect of content regulation is not implemented by RRI. RRI development can be found by the aspects. There are institutional aspect, programs and financial. Every public broadcasting such as RRI Banjarmasin must to be obedient to regulation. Based on regulation, researcher do analyse the implementation of PP No.12 Tahun 2005 by RRI Banjarmasin. Aim of the research to evaluate and analyse the strength and weakness factors on three aspects of PP No.12 Tahun 2005 at RRI Banjarmasin. The research is case study by qualitative methods. observation and interview are used to collect data. The result of the research at RRI Banjarmasin show the implementation of PP No. 12 Tahun 2005 is effective in program aspect and in financial is optimal on operasional but not on broadcast infrastructure. Institutional aspect not optimal especially on employe regeneration.